Application of the V Diagram Method in Translating The Song Wie Schön Du Bist by Students of the Department of German Literature Faculty of Letters, Universitas Negeri Malang - Joseph Bagus Sugiarto; Rosyidah Rosyidah (Universitas Negeri Malang, 2020)
AbstractThe purpose of this study is to describe the translation method that used by students of the German Literature Department, State University of Malang in translating the song